Prophecy and the politics of salvation in late Georgian England : the theology and apocalyptic vision of Joanna Southcott /: the theology and apocalyptic vision of Joanna Southcott. (2015) - Niblett, Matthew I (Matthew Iain), 1979-
No abstract available